Modeling and Simulation of Induction Motor- Submersible Pump System with V/f Algorithm under Stator Short Circuit (SSC) Fault - Alkaoud, Ahmed Mohammad Khier (Journal of engineering sciences and information technology, 2025)
Three-Phase Induction Motors (IM) has been used widely in AC drives. Rotating machines, like IM’s and Centrifugal Pumps (CP) including Submersible Pump (SMP), play a basic role in industrial applications as desalination stations and petro-chemical industries. This paper aims to study and design the mathematical model of Induction Motor-Submersible Pump (IM-SMP) system, and the simulation of the system done by using Matlab environment. We used V/f control algorithm for pump speed regulation. We presented a study and simulation of Stator Short Circuit (SSC) fault of induction motor. We used a mathematical Sequence Analysis technique for detection the SSC fault. The simulation results showed ability and efficient of drive system algorithm for achieving the research goals, such as regulation of pump speed at different load torques, and overcoming some system faults such as, no load pump operation, and SSC fault. The simulation results showed the current, speed, torque and flow rate waveforms compared with a healthy motor state. The simulation results showed a variation on the negative component in sequence analysis as pointer to SSC fault.